Optimising the human experience : the lived world of nursing the families of people who die in intensive care : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Nursing at Massey University - Andrew, Catherine (Massey University, 1997)
Intensive Care nurses share some of the most precious and poignant moments with people who have family members dying in ICU. This study explores the lifeworld of seven ICU nurses who describe their experiences working with these families. Data was gathered using unstructured, indepth, face-to-face interviews. These were tape-recorded and transcribed. The study uses a phenomenological approach informed by Heidegger and hermeneutics. Van Manen's methodological suggestions are followed to shape and focus the study, and provide guidelines for analysis of the data and the writing of the report. The findings reveal that ICU nurses recognise that this is a particularly tragic and difficult time in peoples' lives. The nurses are aware that the last hours or days with a dying relative may be vividly remembered for years to come. During this time nurses seek to optimise the human experience of the family members by making the time as positive, or best, as possible. This is achieved through strategies such as Being There, Supporting, Sharing, Involving, Interpreting and Advocating. These strategies are enabled by three domains: Nurse as Person, Nurse as Practitioner and Nurse as Colleague which describe a wider context to working effectively with families rather than merely looking at direct interactions between the nurse and the family. Optimising the Human Experience is proposed as the central essence or phenomenon of nursing the families of people who die in ICU.
Keywords: Intensive care nursing; Nurse and patient; Death; Family relationships; Critical illness